Implementation of the Accelerated Stunting Reduction Program (Case Study of Dayak Village, Banyumas District and Sempor Lor Village, Purbalingga District) - Ranjani, Ranjani; Aepama, Deka; Permana, Doni Agustia; Lestari, Aprilliani Dwi (Jurnal Administrasi Publik, 2024)
Indonesia is a developing country that has a fairly high prevalence of stunting among its poor households. One of the efforts made by the government to deal with this problem is through an accelerated stunting reduction program. Sempor Lor Village, Purbalingga Regency is one of the villages categorized as successful in dealing with stunting. In contrast to Sempor Lor Village, Dayak Village, Karang Klesem Village, Banyumas Regency still faces various poverty problems, which also indicates the high prevalence of stunting there. This research aims to describe the implementation process of the stunting reduction acceleration program in Sempor Lor Village and Dayak Village, as well as how the stunting reduction acceleration program works for handling stunting in general. This research uses a qualitative approach with a case study method. The results of this research show that the implementation process of the stunting reduction acceleration program in Sempor Lor Village was carried out using a bottom up approach and was categorized as successful. The success of this implementation is supported by many factors, such as consistent village government commitment, active community participation, implementation of sustainable community empowerment efforts through various assistance. In contrast to Sempor Lor Village, the implementation of the stunting reduction acceleration program in Dayak Village, Purbalingga Regency was actually carried out using a top down approach, namely by relying only on central government instructions. Until now, the program implementation process still faces various obstacles, such as limited human resources to become Posyandu Cadre volunteers, low levels of community participation in various mentoring activities.